Penerapan Metode K-Means Untuk Memprediksi Pola Kedatangan Penduduk di Kota Jakarta - Dhimas Hernandi; Arief Jananto (STMIK Banjarbaru, 2023)
Population density in an area has the potential to provoke complex problems, the arrival of people from one area to another in large numbers also has the potential to cause unequal distribution of population on an island. The city of Jakarta in January to May 2021 recorded the arrival of a population of 52,309, the impact of this large number of arrivals will greatly affect the quality of life and the density of mobility in an area. This article examines the use of the K-Means Clustering algorithm to classify the number of arrivals to the city of Jakarta by urban villages. 267 urban villages in the city of Jakarta on population arrival data during January to May 2021 implemented in the K-Means algorithm to determine 3 groups of average number of arrivals (low, medium and high). Each group will represent the pattern of arrivals in each month based on the average arrival and the average in 5 months from January to May 2021. The test results found a increase in arrivals in March in all groups.Kata kunci: Population; Arrival; Urban Villages; K-Means Algorithm Abstrak Kepadatan penduduk dalam suatu daerah berpotensi menimbulkan masalah yang kompleks. Kedatangan penduduk dari satu daerah ke daerah yang lain dalam jumlah yang besar juga berpotensi terhadap timpangnya sebaran penduduk di suatu pulau. Kota Jakarta pada bulan Januari hingga Mei tahun 2021 tercatat kedatangan penduduk sebanyak 52.309, dampak dari kedatangan dalam jumlah besar ini akan sangat berpengaruh terhadap kualitas hidup dan padatnya mobilitas pada suatu daerah. Artikel ini menguji penggunaan algoritme K-Means Clustering untuk mengelompokkan jumlah kedatangan penduduk ke kota Jakarta berdasarkan kelurahan. 267 kelurahan di kota Jakarta pada data kedatangan penduduk selama Januari hingga Mei 2021 diimplementasikan pada algoritme K-Means untuk menentukan 3 kelompok rata-rata jumlah pendatang (rendah, menengah dan tinggi). Setiap kelompok akan merepresentasikan pola kedatangan di tiap bulannya berdasarkan rata-rata kedatangan dan rata-rata dalam 5 bulan dari Januari hingga Mei 2021. Hasil pengujian mendapati lonjakan kedatangan pada bulan Maret pada semua kelompok.Kata kunci: Sebaran penduduk; Kedatangan; Kelurahan; Algoritme K-Means Clustering